Daclatasvir Combined with Peginterferon Alfa-2A and Ribavirin in Japanese Patients Infected with Hepatitis C Genotype 1. Issue 5 (July 2014) - Izumi, Namiki; Yokosuka, Osamu; Kawada, Norifumi; Osaki, Yukio; Yamamoto, Kazuhide; Sata, Michio; Ishikawa, Hiroki; Ueki, Tomoko; Hu, Wenhua; McPhee, Fiona; Hughes, Eric A; Kumada, Hiromitsu
Background: New direct-acting antiviral agents are currently being developed to treat chronic HCV. The efficacy and safety of daclatasvir combined with peginterferon alfa-2a (alfa-2a) and ribavirin were assessed in a randomized, double-blind Phase IIa study of Japanese patients with chronic HCV genotype-1 infection. Methods: Japanese patients who were treatment-naive ( n =25) or prior null ( n =12) or partial ( n =5) responders received once-daily daclatasvir 10 mg or 60 mg or placebo in combination with alfa-2a and ribavirin. Daclatasvir recipients with a protocol-defined response (HCV RNA<15 IU/ml at week 4 and undetectable at week 12) were treated for 24 weeks; placebo recipients and patients without a protocol-defined response were treated for 48 weeks. Results: Sustained virological response at 24 weeks post-treatment (SVR24 ) was achieved by 89% and 100% of treatment-naive patients receiving daclatasvir 10 mg and 60 mg, respectively, versus 75% in placebo recipients. Virological failure was more frequent in prior non-responder patients, with 50% and 78% achieving SVR24 in daclatasvir 10 mg and 60 mg groups, respectively. Adverse events occurred with similar frequency among treatment groups and were consistent with the adverse event profile of alfa-2a/ribavirin alone. The most commonly reported adverse events included pyrexia, alopecia, anaemia, lymphopenia, neutropenia, pruritus and diarrhoea. Three patients discontinued treatment due to anaemia. Conclusions: Daclatasvir combined with alfa-2a/ribavirin in treatment-naive patients showed greater efficacy than alfa-2a/ribavirin alone and was generally well tolerated. The 60-mg dose of daclatasvir achieved the highest rates of SVR24 in both treatment-naive and non-responder populations and will be evaluated in a Phase III clinical trial.